The Export Strategy of PT. Dagsap Endura Eatore Yogyakarta for Entering Asean International Market - Khusaini Wijayanto; Dwidjono Hadi Darwanto; Lestari Rahayu Waluyati (Faculty of Agriculture, Universitas Gadjah Mada jointly with PISPI, 2016)
This study aimed to determine the position of PT. Dagsap Endura Eatore Yogyakarta and to formulate the export strategy to enter the international market of ASEAN. The primary and secondary data were used in this study. The SWOT analysis, consisted of four indicators i.e strengths, weakness, opportunities, and threats, was used for analysis data. The results showed that the total of weighting score for force factor of PT. Dagsap Endura Yogyakarta Eatore was 4.45; the vulnerability factor was 4.07; odds factor was 4.70; and threats factor was 4.11. The current PT. Dagsap Endura Eatore Yogyakarta is in quadrant 1 (one) SWOT matrix that supports an aggressive growth policy (Growth Oriented Strategy). Export strategy for PT. Dagsap Endura Eatore Yogyakarta should use the power, so that it can seize the export opportunities to enter the international market of ASEAN.